PREDICTION OF PRICES FOR AGRICULTURAL PRODUCTS THROUGH MARKOV CHAIN MODEL. - UktamUmurzakov (International Journal of Psychosocial Rehabilitation, 2020)
Currently, all producing countries face big problems with determining production volumes because they have a problem related to predicting consumer prices in the future. In fact, the consumer prices are strong fluctuations in the market due to these being directly related to the season. Many developing countries have already done this problem, as these countries used many methods to forecast agricultural production volumes and prices. Producing agricultural products is related to many causes, including natural factors, and the scientists results also influence the prediction of total volumes. Nowadays, the scientists and researchers are using many factors to forecast the changeable prices in the future. While using many methods has not taken good results, because the production of agricultural goods prices is also directly connected to the time factor, using the Markov Chain model is more efficient to predict prices in the future. Production commodities are related to many factors in the agricultural sector, so the price of goods may strongly change in a short time, whether it is rising, going down, or remaining unchanged. One must not forget that it is important to analyze each case and select an alternative to the benefit of all subjects, who also are producers, intermediaries, and consumers.